Digital Media Integration in School Public Relations: Strategies for Marketing and Educational Services in Vocational Schools - Nadia Muliawati; Priadi Surya (Universitas Pendidikan Ganesha, 2026)
This research is motivated by the problem of low optimization in the use of digital media in school public relations (PR) strategies, resulting in an underutilized image of the institution, ineffective communication, and limited reach of educational services. This study employs a qualitative approach with a multi-case design to investigate the practice of digital media implementation in public relations activities. This study aims to analyze how digital PR strategies are employed to construct institutional image, enhance public engagement, and strengthen industry collaboration. The research subjects consisted of 14 informants, including the deputy principal for public relations, teachers, students, alums, and community members, who were selected purposively. Data were collected through in-depth interviews, non-participatory observations, and documentation studies, then analyzed using the Miles and Huberman interactive model. The results of the study demonstrate that digital media integration is achieved through the use of social media, school websites, video publications, and online platform-based communication services, which significantly enhance the effectiveness of branding, expand information accessibility, and strengthen partnerships with the public. This strategy also contributes to increasing information accessibility, enhancing service transparency, and enhancing the effectiveness of educational marketing. It was concluded that the integration of digital media plays a strategic role in maintaining a school’s image, public trust, and competitiveness. The implications of this study underscore the need to enhance digital literacy among educators and public relations teams, enabling the implementation of digital media in a more professional, systematic, and sustainable manner.